Atorvastatin rescues pulmonary artery hypertension by inhibiting the AKT/ERK-dependent PDGF-BB/HIF-1α axis - Chen, Jianfei; Song, Mingbao; Qian, Dehui; Liu, Linqiong; Yang, Kun; Shou, Yunfeng; Zhao, Hanru; Zhang, Li (Panminerva medica, 2024)
The aim of this study is to explore the role of atorvastatin in rescuing pulmonary artery hypertension (PAH) by inhibiting the AKT/ERK-dependent PDGF-BB/HIF-1α axis. PAH model in rats was established by MCT induction, followed by Atorvastatin intervention. Pulmonary hemodynamic measurement and pulmonary morphological evaluation in rats were conducted. Human pulmonary artery smooth muscle cells (hPASMCs) were subjected to hypoxic exposure or PDGF-BB treatment, followed by atorvastatin induction. Relative levels of HIF-1α, p-ERK and p-Akt were detected. Viability and apoptosis were respectively determined by cell counting kit-8 (CCK-8) assay and flow cytometry. Atorvastatin protected PAH-induced increases in RVSP and Fulton's index in rats. Meanwhile, it inhibited vascular remodeling following PAH by downregulating HIF-1α and PDGF-BB. Hypoxia or PDGF-BB treatment in hPASMCs resulted in upregulation of p-ERK and p-Akt, and viability increase, which were partially abolished by Atorvastatin intervention. In addition, atorvastatin triggered apoptosis in hypoxia or PDGF-BB-induced hPASMCs. Atorvastatin inhibits the activation of HIF-1α and proliferative ability, and triggers apoptosis in hPASMCs exposed to hypoxia or PDGF-BB treatment through inactivating the AKT/ERK pathway.